Strain relaxation in epitaxial Ge crystals grown on patterned Si(001) substrates. (15th January 2017) - Arroyo Rojas Dasilva, Yadira; Rossell, Marta D.; Isa, Fabio; Erni, Rolf; Isella, Giovanni; Känel, Hans von; Gröning, Pierangelo
Abstract: In this paper we report on the defects formed in Ge crystals grown on Si(001) pillars upon strain relaxation. The analysis is performed by high-angle annular dark-field scanning transmission electron microscopy. The strain relaxation happens by means of 60° and 90° misfit dislocations with Burgers vectors b → = 1 2 ⟨ 110 ⟩ . Misfit dislocations may split forming partial dislocations with Burgers vectors b → = 1 6 ⟨ 112 ⟩, and are separated by a stacking fault. Besides, intrinsic stacking faults in different 111 planes interact and annihilate each other forming stair rod dislocations. Coherent and incoherent twin boundaries of the Σ 3111 and Σ 3112 types are also found in the Ge. Graphical Abstract: